THE SELECTION OF ALTERNATIVES TRAINING SHIP TO SUBSTITUTE KRI DEWARUCI FOR NAVAL ACADEMY CADETS USING THE ANALYTIC NETWORK PROCESS (ANP) METHOD - Sukmo Hadi Nugroho; Adi Bandono; Okol Sri Suharyo; Raditya Novianto (Indonesian Naval Technology College - Sekolah Tinggi Teknologi Angkatan Laut - STTAL, 2020)
Republic of Indonesia Ship (KRI) Dewaruci is a Naval Academy Cadets' (AAL) training ship that is old. Thiscondition is very susceptible to various threats of accidents while carrying out voyages around the world to cruisethe AAL Kartika Jala Krida Kadet. The government has planned to replace KRI Dewaruci with a new trainingship. This study aims to determine the selection of new prospective makers training ship by the Analytic NetworkProcess (ANP) method. This ANP method is used because the existing data have a relationship among thecriteria and the relationship between criteria and sub-criteria. In alternative selection, there are two main criteria,namely operational requirements criteria with four sub-criteria: security, geographical conditions, skills training,transfer of technology and technical requirement criteria with five sub-criteria: machinery, navigation, trainingequipment, platform, masts, and sails. The results of this study are the alternative priorities for new training shipreplacing the best KRI Dewaruci and also the priority of the main/critical sub-criteria. The biggest alternativescore value is a training ship made by Piere Shipyard made in Spain with a score of 0.50259.Keywords: Analytic Network Process (ANP), Super Decisions, Training ship, Criteria and Sub-criteria